Determination of Salbutamol Using Spectrophotometric Method Depending on Chromium-1,5-diphenylcarbazide Complex - Enas S. Thanon; Bassima A. A. Saleem; Najih H. Shikho (Tikrit Journal of Pure Science, 2020)
A  rapid, simple, accurate, and economized spectrophotometric method for the determination of salbutamol sulfate(SAL)  has been suggest using an oxidation-reduction reaction.  This method depends on the oxidation of SAL medication with an excess amount of chromate (CrO42- ) as an oxidant agent in the acidic medium of 2N Sulphuric acid and the presence of Sodium oxalate as a catalyst of the oxidation process. Then the remaining quantity of chromate will be reacted with 1,5-diphenylcarbazide to form a pink-reddish and stable water-soluble complex which is exhibiting maximum absorption at 543 nanometers. The optimum conditions for the present work were studied experimentally. The linearity of the proposed method follows Beer’s law in the concentration range of 50 to 900 μg in a final volume of 25ml with a molar absorptivity which is equal to 0.538×104 l.mol-1.cm-1. The proposed method shows good recovery values,  accuracy, and precision. The present method was so good to be successfully applied for the determination of SAL medication in its pure form and pharmaceutical preparations.